Analysis of Papua Provincial Government's Implementation of Accrual-Based Local Government Financial Reporting - Sonjaya, Yaya (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study aims to investigate the effect of education level, work experience, training, and position on the implementation of accrual-based financial reporting in the Regional Apparatus Organizations (OPDs) of Papua Province. Research Design and Methodology: A quantitative approach was employed, utilizing primary data collected through questionnaires from 70 financial officers across 35 operating departments (OPDs). Variables were measured with a five-point Likert scale. Data analysis involved descriptive statistics, classical assumption tests, and multiple linear regression analysis. Findings and Discussion: The results indicate that all four variables have a significant and positive impact on the implementation of accrual-based financial reporting. Training was found to be the most influential factor. The model accounts for 92% of the variance in the dependent variable, emphasizing the critical role of human resource quality in public sector financial reporting. Implications: The findings suggest the need to strengthen employee competence through targeted training, align job roles with expertise, and minimize personnel rotation. This supports better financial governance and sustained application of accrual-based reporting. Future research should investigate additional factors, including information systems, technological support, and organizational environment.